Static, dynamic balance and functional performance in subjects with and without plantar fasciitis - Geiseane Aguiar Gonçalves; Danilo Harudy Kamonseki; Bruna Reclusa Martinez; Maythe Amaral Nascimento; Império Lombardi Junior; Liu Chiao Yi
Abstract Introduction: Plantar fasciitis (PF) is characterized by non-inflammatory degeneration and pain under the heel, and is one of the most common foot complaints. The compensations and adjustments made to decrease the discomfort caused by the disease are clinical findings and can be a factor that contributes to impaired balance and decreased functional performance. Objective: To compare functional performance as well as static and dynamic balance among subjects with and without PF. Methods: The sample consisted of 124 subjects of both sexes aged 20-60 years. Participants were divided into two groups: a bilateral PF group (PFG; n = 62) and a control group (CG, n = 62). The following outcomes were analyzed: static and dynamic balance (using functional tests) and functional performance (using a questionnaire). We used Student's t test for independent samples to compare variables between the groups. The alpha error was set at 0.05. Results: Subjects with PF showed greater impairment in their overall dynamic balance performance (p < 0.001) than the control group, except for left posteromedial movement (p = 0.19). The CG showed showed better functional performance (p < 0.001) than the PF group. There was no difference between groups for the variable static balance on stable (p = 0.160) and unstable surfaces (p = 0.085). Conclusion: Subjects with PF displayed smaller reach distances in the overall Star Excursion Balance Test (SEBT), demonstrating a deficit in dynamic balance and functional performance when compared with healthy subjects.